Escherichia coli expression and purification of four antimicrobial peptides fused to a family 3 carbohydrate-binding module (CBM) from Clostridium thermocellum - Guerreiro, Catarina I. P. D. (2008)
Antimicrobial peptides (AMPs) are molecules that act in a wide range of physiological defensive mechanisms developed to counteract bacteria, fungi, parasites and viruses. Several hundreds of AMPs have been identified and characterized. These molecules are presently gaining increasing importance, as a consequence of their remarkable resistance to microorganism adaptation. Carbohydrate-binding modules (CBMs) are non-catalytic domains that anchor glycoside hydrolases into complex carbohydrates. Clostridium thermocellum produces a multi-enzyme complex of cellulases and hemicellulases, termed the cellulosome, which is organized by the scaffoldin protein CipA. Binding of the cellulosome to the plant cell wall results from the action of CipA family 3 CBM (CBM3), which presents a high affinity for crystalline cellulose. Here CipA family 3 CBM was fused to four different AMPs using recombinant DNA technology and the fusion recombinant proteins were expressed at high levels in Escherichia coli cells. CBM3 does not present antibacterial activity and does not bind to the bacterial surface. However, the four recombinant proteins retained the ability to bind cellulose, suggesting that CBM3 is a good candidate polypeptide to direct the binding of AMPs into cellulosic supports. A comprehensive characterization of the antimicrobial activity of the recombinant fusion proteins is currently under evaluation.